Quinolinyl β-enaminone derivatives exhibit leishmanicidal activity against Leishmania donovani by impairing the mitochondrial electron transport chain complex and inducing ROS-mediated programmed cell death. (7th December 2022) - Rani, Ankita; Khanikar, Shilpika; Dutta, Mukul; Katiyar, Shivani; Qamar, Tooba; Seth, Anuradha; Agnihotri, P K; Guha, Rajdeep; Vishwakarma, Jai N; Kar, Susanta
Abstract: Objectives: Previously, a series of side chain-modified quinolinyl β-enaminones was identified to possess significant activity against chloroquine-sensitive or -resistant Plasmodium falciparum and Brugia malayi microfilariae. The present study evaluates in vitro and in vivo activity of the series against Leishmania donovani and reports their mode of action. Methods: The in vitro activity of 15 quinolinyl β-enaminone derivatives against Leishmania promastigotes and amastigotes was assessed by luciferase assay. The reduction of organ parasite burden was assessed by Giemsa staining in L. donovani -infected BALB/c mice and hamsters. Intracellular Ca 2+ and ATP level in active derivative (3D)-treated promastigotes were determined by fluorescence and luminescence assays. Flow cytometry was performed to determine loss of mitochondrial membrane potential (MMP) using JC-1 dye, reactive oxygen species (ROS) generation using 2′, 7′-dichlorodihydrofluorescein diacetate (DCFDA) dye, phosphatidylserine externalization by Annexin V-FITC staining and cell-cycle arrest by propidium iodide (PI) staining. Results: Compounds 3A, 3B and 3D showed significant in vitro efficacy against L. donovani with IC50  < 6 µM and mild cytotoxicity (∼75% viability) at 25 µM on J774 macrophages. 3A and 3D at 50 mg/kg and 100 mg/kg reduced parasite burden (>84%) in infected mice and hamsters, respectively, whereas 3D-treated animals demonstrated maximum parasite burden reduction without organ toxicity. Mode-of-action analysis revealed that 3D induced apoptosis by inhibiting mitochondrial complex II, reducing MMP and ATP levels, increasing ROS and Ca 2+ levels, ultimately triggering phosphatidylserine externalization and sub-G0/G1 cell-cycle arrest in promastigotes. Conclusions: Compound 3D-mediated inhibition of L. donovani mitochondrial complex induces apoptosis, making it a promising therapeutic candidate for visceral leishmaniasis.